2016
DOI: 10.1364/oe.24.019278
|View full text |Cite
|
Sign up to set email alerts
|

Optical vortex generation with wavelength tunability based on an acoustically-induced fiber grating

Abstract: We presented a method to actualize the optical vortex generation with wavelength tunability via an acoustically-induced fiber grating (AIFG) driven by a radio frequency source. The circular polarization fundamental mode could be converted to the first-order optical vortex through the AIFG, and its topological charges were verified by the spiral pattern of coaxial interference between the first-order optical vortex and a Gaussian-reference beam. A spectral tuning range from 1540 nm to 1560 nm was demonstrated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(41 citation statements)
references
References 29 publications
0
38
0
3
Order By: Relevance
“…Existing ways to generate OAM modes are usually based on free-space coupling methods, such as cylindrical-lens mode converters [4], spatial light modulators [5], integrated silicon devices [6], and micrometer-scale metamaterials [7]. Researchers have recently demonstrated various all-fiber OAM generators based on standard single-mode fibers (SMFs) [8], few-mode fibers [9][10][11][12][13][14][15], photonic crystal fibers (PCFs) [16,17], and other special types of fibers [18,19]. For example, the authors recently reported on an OAM convertor based on a helical long-period fiber grating inscribed by means of twisting a standard SMF [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Existing ways to generate OAM modes are usually based on free-space coupling methods, such as cylindrical-lens mode converters [4], spatial light modulators [5], integrated silicon devices [6], and micrometer-scale metamaterials [7]. Researchers have recently demonstrated various all-fiber OAM generators based on standard single-mode fibers (SMFs) [8], few-mode fibers [9][10][11][12][13][14][15], photonic crystal fibers (PCFs) [16,17], and other special types of fibers [18,19]. For example, the authors recently reported on an OAM convertor based on a helical long-period fiber grating inscribed by means of twisting a standard SMF [8].…”
mentioning
confidence: 99%
“…For example, the authors recently reported on an OAM convertor based on a helical long-period fiber grating inscribed by means of twisting a standard SMF [8]. A few researchers have demonstrated OAM 1 and OAM 2 convertors based on two- [9][10][11] and four-mode fibers [12][13][14][15], respectively. Moreover, Wong et al demonstrated, for the first time, excitation of OAM resonances in a helically twisted standard solid-core hexagonal PCF, but no OAM modes were experimentally observed in such a twisted PCF [16].…”
mentioning
confidence: 99%
“…By tuning the voltage and frequency of the radio frequency (RF) driving signal applied to the acoustic transducer (AT), an AIFG is produced by the propagation of the linearly polarized acoustic flexural wave along the unjacketed TMF [25]. When the BLS transmits along the acousto-optic interaction region of the AIFG, the fundamental vector mode (HE x/y 11 ) can be coupled to the first-group of high-order vector modes (TE01, HE e/o 21 , TM01) with the phase-matching condition LB= to be satisfied, where LB=λ/Δneff is the beat length between HE…”
Section: Resultsmentioning
confidence: 99%
“…2(a). The grating length of the FBG is 50 mm, and the fiber diameter was etched to 30 m with hydrofluoric (HF) acid to increase the acousto-optic coupling efficiency [26,27]. The tip of the aluminum horn was reduced to the diameter same as that of the FBG and subsequently glued to the FBG with UV epoxy.…”
Section: Results and Dicussionsmentioning
confidence: 99%